Assessing the impact of corporate entrepreneurship in the financial performance of subsidiaries of Colombian business groups: Under environmental dynamism moderation - Antonio Rodríguez-Pe\~na (Journal of Innovation and Entrepreneurship, 2021)
Corporate entrepreneurship creates opportunities in employment, technological advances, value creation, and cultural transformation for entrepreneurial ecosystems, entrepreneurs, governments, economies, and society around the globe. The purpose of this study is to assess the impact of corporate entrepreneurship on the financial performance of subsidiaries in Colombian business groups under the moderating effect of the environmental dynamism, because the relationship between corporate entrepreneurship and financial performance in emerging economies must differ from developed economies. Using a cross-sectional structural equation modeling analysis, this study assessed the impact of entrepreneurial orientation and corporate venturing on the firm financial performance of 87 subsidiaries of Colombian business groups at different levels of environmental dynamism. This study also confirms that the relationship between corporate entrepreneurship and performance is context-dependent and that entrepreneurial orientation has a strong and positive causal relationship with corporate venturing. Additionally, subsidiaries of Colombian business groups increase their financial performance when also does the entrepreneurial orientation, and decrease financial performance when so does corporate venturing. Furthermore, the results show that environmental dynamism does not have a moderating effect on the relationship between corporate entrepreneurship of subsidiaries in Colombian business groups and their performance. This paper would contribute to important areas in Latin America business, where such studies are scarce.
Keywords: 650; Business group; Colombia; Corporate entrepreneurship; Corporate venturing; Emerging economies; Emerging market firms; Entrepreneurial orientation; Environmental dynamism; SmartPLS